DASAR PERTIMBANGAN PENUNTUT UMUM DALAM PENGAJUAN PENINJAUAN KEMBALI PERKARA PIDANA (Putusan MA No.70/Pid.B/ 2010/PN. Kpg tanggal 21 Juni 2010) - Noven Verderikus Bulan (Faculty of Law, Universitas Diponegoro, 2014)
This thesis will discuss issue concerning basic consideration of public prosecutor to appeal juridical review to the Supreme Court and the impact of the absence of legal authority to appeal to the public prosecutor. Methods applied in this research comprise a normative juridical approach where law matters are used (Statute Approach) to examine the rules relating to the juridical review. This study applies also concepts (Conceptual Approach) to analyze basic consideration of the prosecuting attorney in appealing juridical review, and case study (Case Approach) to determine law cases related to the juridical review appealed by the public prosecutor. The result of this study indicates that the basic considerations of public prosecutor in appealing a criminal case to the Supreme Court comprise justice, legal certainty and usefulness factors